APPLICATION OF HEC-RAS FOR ANALYSIS OF FLOOD ZONES - Gjeshovska, Violeta; Ilioski, Bojan (University Ss. Cyril and Methodius in Skopje, 2021)
Timely forecasting of floods and floodplains allows measures to be taken to prevent or reduce their occurrence and/or to provide protection against their harmful effects. The flood wave from increase of the water level and the flow in the riverbed is defined as a non-stationary flow, which results in flooding of riverbeds. The use of hydraulic models to conduct flood simulations is a common practice and widely accepted for rapid and accurate definition of flood zones. In the investigations presented in this paper, the HEC-RAS (1D, 2D, 1D / 2D) software package has been used to simulate different flood scenarios related to Vardar River. Using the HEC-RAS software package, 1D, 2D and a combination of 1D and 2D models of a non-stationary flow have been formulated by defining the initial and the boundary conditions separately for each model. As a result of the simulation of the flood wave propagation through the riverbed, the flood zones and the most endangered areas have been defined. The obtained results and the differences among the considered models have been analyzed in order to see which model is the most appropriate for the case of a flood wave. From the hydraulic analyses carried out by use of all three models, it is concluded that the riverbed of the Vardar river in the considered section has a very low transportation capacity and that there are flood zones along the entire length of the river. The riverbed of the Vardar river in the analyzed region, from the village Tudence to the village Jegunovce, can safely transform flows up to Q=62 m3/s.
Keywords: flood, flood wave, flood zones, HEC-RAS.